The neutron diffraction studies of a crystal structure of nafe(wxmo1-xo4)2 (x = 0.5; 0.75) at low temperature - Thanh, V. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2016)
The crystal structure of the double tungstates NaFe(W0.5Mo0.5O4)2 and NaFe(W0.75Mo0.25O4)2 has been studied by means of a neutron diffraction method in temperature range 5-24 K. No evidence for long range magnetic order was found in both compounds down to 5 K. The unit cell parameters, atomic coordinates, bond lengths and angles for the studied compounds have been obtained. An absence of magnetic ordering is explained by reduction of super-exchange coupling due to a disordering of a Fe-O-O-Fe trapeze-like crystal unit.